Risk Factors of Smartphone Addiction on Pre-School Children in Indonesia: Path Analysis - Lidia Aditama Putri; Nurun Nikmah; Munisah Munisah; Diyana Faricha Hanum; Rizky Maharja; Aidha Rachmawati; Diani Octaviyanti Handajani; Hilda Indriani; Rani Rosita (NHM PRESS, 2022)
Generally, parents have introduced smartphones as their children’s learning facility, whereas children are groups of high risk for addiction. This study aims to analyze the risk factors of smartphone addiction on pre-school children. A cross-sectional study was conducted on 1392 mothers with children aged 3-6 years. The data were collected by using a questionnaire. The data were analyzed bivariate with chi-square by IBM SPSS 22 software and multivariate with path analysis by IBM STATA 13 software. The directly factors which make children addicted to smartphone are mother’s age (b= 2.12; CI 95%= 1.68-2.69; p= 0.000), mother’s occupation (b= 1.69; CI 95%= 1.35-2.12; p= 0.000), parents’ control (OR= 1.93; 95% CI= 1.55 to 2.40; p= 0.000), and smartphones ownership by children (OR= 1.69; 95% CI= 1.31 to 2.17; p= 0.000). Mother’s education, rules of smartphone usage in the family and rules of smartphone usage at school affects on children addicted to smartphone indirectly. There is a direct effect of mother’s age, mother’s occupation, parents’ control on the smartphone usage and smartphones child’s personal smartphone to the risk of smartphone addiction to pre-school children. Meanwhile, there is an indirect effect on a mother’s education, rules of smartphone usage in the family, and school effects to the risk of smartphone addiction to pre-school children.